Evolution of the American Zero Energy House - Russell, Stanley (International Journal of Sustainable Construction Engineering and Technology, 2011)
Interest in reducing energy use in buildings began in the U.S. in the 1930 with work at the Massachusetts Institute of Technology on solar heated structures. With the energy crises in the 1970s, efforts were made to reduce energy use in U.S. homes. Passive solar design involved insulated south oriented glazing systems, Trombe walls, sunspaces, flat plate collectors; thermal mass and optimally designed overhangs. It was discovered that by reducing building cooling and heating needs through energy conservation while implementing passive solar strategies the lowest energy use at a lower incremental cost could be achieved. Super-insulated homes were successful at minimizing heat loss and gain and the subsequent load on mechanical systems, but interest subsided as energy prices dropped in the 1980s. The passive solar homes and super-insulation movements, addressed passive heating and cooling, but other home energy end uses were not addressed. Throughout the late 1980s, the cost of solid state solar electricity production with photovoltaic cells declined and become affordable for individual house distributed generation. This paper is a survey of the evolution of the Zero Energy House in the U.S. and the related technologies from its experimental beginnings to its realization in several recent projects.